On the Performance of a Photonic Reconfigurable Electromagnetic Band Gap Antenna Array for 5G Applications - Elwi, Taha A.; Taher, Fatma; Virdee, Bal S.; Alibakhshikenari, Mohammad; Zuazola, Ignacio J. Garcia; Krasniqi, Astrit; Kamel, Amna Shibib; Tokan, Nurhan Turker; Khan, Salahuddin; Parchin, Naser Ojaroudi; Livreri, Patrizia; Dayoub, Iyad; et al. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2024)
In this paper, a reconfigurable Multiple-Input Multiple-Output (MIMO) antenna array is presented for 5G portable devices. The proposed array consists of four radiating elements and an Electromagnetic Band Gap (EBG) structure. Planar monopole radiating elements are employed in the array with Coplanar Waveguide Ports (CWPs). Each CWP is grounded on one side to a reflecting L-shaped structure that has an effect of improving the antenna's directivity. It is shown that by inductively connecting Minkowski fractal structure of $1 >{st}$ order to the radiating element, the impedance matching is improved that results in enhancement in the array's bandwidth performance. The EBG structure is used to provide the isolation between antenna elements in the MIMO array. The fractal structure is connected to the L-shaped reflector through four photosensitive light dependent resistor (LDR) switches. The effect of various LDR switching configurations on the performance of the antenna is investigated. The proposed array provides a novel performance in terms of S-parameters with enhancements in the radiation properties. Such enhancements
Keywords: Periodic structures; Metamaterials; Antenna arrays; MIMO communication; Integrated circuit modeling; Antennas; Analytical models; Electromagnetics; 5G mobile communication; Specific absorption rate; Electromagnetic Band Gap (EBG); multiple-input multiple-output (MIMO); 5G system; specific absorption rate (SAR); photosensitive light dependent resistor (LDR); Computer Science; Engineering; Telecommunications